AUDIT KEHADIRAN DOSEN PADA PUSAT LAYANAN PERKULIAHAN DAN PELAPORAN (PLPP) DI IBI DARMAJAYA MENGGUNAKAN FRAME WORK COBIT 4.1. - -, Amnah (Jurnal Informatika, 2014)
This research was undertaken in order to find out the punctuality of the lecturersâ teaching at IBI Darmajaya from which its evaluation was conducted by the lecturing and reporting service center. During this time, the activity related to the audit of the punctuality of the lecturersâ teaching had not been done. Therefore, the researcher believed that this was an opportunity in conducting the research in the lecturing and reporting service center. The audit was carried out as a measure of the successfulness of the implementation of the discipline of the human resource and the result of the socialization towards the lecturers in the beginning of each semester prior to the lecturing activity. The results of these activities were expected to help the involved division map the lecturers who were much disciplined and the lecturers who had a lack of discipline in order to take a good solution for both. The audit activity was interviewing the head of the related bureau and the head of the lecturing and reporting service center and distributing questionnaires with two levels. The first level was for the users (the students) and the second level was for the management divisions (the administrative bureau of academic and student affairs, the head of lecturing and reporting service center and the chairman of the department of IBI Darmajaya).Keywords: Audit, Maturity, Users